2012
DOI: 10.1074/jbc.m112.394544
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase-1 (HDAC1) Is a Molecular Switch between Neuronal Survival and Death

Abstract: Background:The role of HDAC1 in the regulation of neuronal survival is unresolved. Results: In cooperation with HDRP, HDAC1 promotes neuronal survival, but when it interacts with HDAC3, HDAC1 promotes neuronal death. Conclusion: HDAC1 can protect neurons or promote neuronal death depending on whether it interacts with HDRP or HDAC3. Significance: Our results provide insight into the role of HDAC1 in the regulation of neuronal survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 37 publications
3
111
0
1
Order By: Relevance
“…One of the most promising is inhibition of histone deacetylases (HDACs). HDACs appear to play important roles in neuronal survival ( 158,159 ). HDAC inhibitors have already been approved for clinical use in humans for treatment of certain cancers.…”
Section: Cyclodextrin As a Therapy For Npc Diseasementioning
confidence: 99%
“…One of the most promising is inhibition of histone deacetylases (HDACs). HDACs appear to play important roles in neuronal survival ( 158,159 ). HDAC inhibitors have already been approved for clinical use in humans for treatment of certain cancers.…”
Section: Cyclodextrin As a Therapy For Npc Diseasementioning
confidence: 99%
“…Generation of Hdac3 Ϫ/Ϫ cKO Mice-Hdac3 Ϫ/Ϫ cKO mice were generated as described previously (10). Briefly, for CNSspecific knockdown, mice homozygous for loxP sites in the HDAC3 locus (Hdac3…”
Section: Mice-hdac3mentioning
confidence: 99%
“…Genotyping-Genotyping of Nes-Cre/HDAC3, Thy1-Cre/ HDAC3, and CaMKII-Cre/HDAC3 cKO mice was performed as described previously (10,12). Briefly, DNA was extracted from mouse toe clips for Thy1-Cre/HDAC3 and CaMKII-Cre/ HDAC3 or tail tissue for Nes-Cre/HDAC3 mice using the REDExtract-N-Amp tissue PCR kit from Sigma-Aldrich (St. Louis, MO), and the DNA obtained was used in PCRs to determine the genotype: HDAC3, GCTTGGTAGCCAGCCAGCT-TAG (forward) and CATGTGACCCCAGACATGACTGG (reverse); Cre, CCCGCAGAACCTGAAGATGTT (forward) and CGGCTATACGTAACAGGGTG (reverse); and Gdf, AAGCCCTCAGTCAGTTGTGC (forward) and AAAAC-CATGAAAGGAGTGGG (reverse).…”
Section: Neo-loxpmentioning
confidence: 99%
“…Previously, the HDAC-related protein (HDRP), a truncated form of HDAC9, was shown to recruit HDAC1 and deacetylate H3 at c-Jun promoter regions, which is dependent upon HDAC1 deacetylase activity (111) . Bardai et al (110) showed that HDAC1 and HDRP associate via HDAC1 N -terminal tails and the neurotoxic HDAC1-HDAC3 interaction is reduced when HDRP expression is elevated, suggesting that HDAC1 is sequestered by HDRP. Taken together, HDAC1 performs as a molecular switch in regulating neuronal fate.…”
Section: Epigenetic Mechanisms and Neuronal Protectionmentioning
confidence: 99%
“…Taken together, this study effectively identified HDAC3 as a potent neurotoxic deacetylase and therefore becomes an attractive target to downregulate in an effort to increase neuronal viability during neurodegeneration (109) . In a subsequent study, the authors showed that HDAC1 contributes to neurodegeneration and is highly neurotoxic, as it complexes with HDAC3 in mediating neuronal death (110) . Previously, the HDAC-related protein (HDRP), a truncated form of HDAC9, was shown to recruit HDAC1 and deacetylate H3 at c-Jun promoter regions, which is dependent upon HDAC1 deacetylase activity (111) .…”
Section: Epigenetic Mechanisms and Neuronal Protectionmentioning
confidence: 99%